A comparison of the structures of >300 °C fractions in six Chinese shale oils obtained from different locations using 1H NMR, 13C NMR and FT-IR analyses. (1st January 2018) - Wang, Qing; Cui, Da; Wang, Ping; Bai, Jingru; Wang, Zhichao; Liu, Bin
Abstract: Structural features of >300 °C fractions of six Chinese shale oils, namely the Huadian, Wangqing, Fushun, Longkou, Maoming and Yaojie oil, have been characterized using 1 H nuclear magnetic resonance, 13 C nuclear magnetic resonance and Fourier transform infrared techniques. Based upon the results obtained from 1 H nuclear magnetic resonance and 13 C nuclear magnetic resonance, the distribution of various types of hydrogen and carbon atoms, and related structural parameters in >300 °C fractions were determined. Different types of functional groups were studied based on the curve-fitting analysis of Fourier transform infrared spectra with Gaussian function. The results showed that the >300 °C fraction of Huadian shale oil had the highest ratio of aliphatic carbon among the six samples. Meanwhile, the average carbon number of substituents in Huadian oil's >300 °C fraction was the highest, and had the value of 8.98. Moreover, the Huadian sample owned the lowest degree of branching of aliphatic chain, whereas it had the highest ratios of CH2 and CH3 . These results indicated that, in Huadian oil's >300 °C fraction, the alkyl carbon chains were longer, whereas the branched chains were less (in number) compared to other samples. Furthermore, the curve-fitting analysis indicated that 2 and 3 adjacent H deformations were dominant in aromatic structures. The oxygen-containing groups in >300 °C fraction of Chinese shale oil were mainly the CO groups, followed by the COH groups, OCO groups and conjugated CO groups. In summary, >300 °C fractions of Chinese shale oils showed similar differences with regards to the elemental compositions and functional groups.